Mudir’s Strategy in Shaping the Religious Character and Discipline of New Santri through a Quarantine Program: A Case Study at Pondok Pesantren Islam Haji Miskin - Muhamad Agus Suryana; Darul Ilmi; Afrinaldi Afrinaldi; M. Arif (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Among educational institutions with distinctive characteristics, Islamic boarding schools (pesantren) represent a unique educational model because of their flexibility in developing innovative and creative management practices. Parents commonly choose pesantren due to concerns about students’ character formation and discipline, making the development of religious character and disciplined behavior a major managerial challenge. This study aims to describe the strategies employed by the mudir in developing the religious character and discipline of new santri through the quarantine program at PPI Haji Miskin and to identify the factors supporting the implementation of these strategies. A descriptive qualitative method was employed, with data collected through interviews, observations, and documentation studies. The findings indicate that the development of students’ religious character and discipline through the quarantine program is implemented through three main strategies: providing selected instructional materials, including daily practical fiqh, Qur’anic tahsin, active Arabic language learning, moral conduct (adab), and self-reliance; establishing habituation practices through systematically scheduled activities; and positioning teachers as role models through Islamic dress, communication using the official pesantren language, worship practices, and exemplary conduct within the boarding school environment. The implementation of the mudir’s strategy is supported by several factors, including the need to accelerate the formation of religious character among new santri, reduce adaptation difficulties during the first month, improve Qur’anic recitation skills, strengthen Arabic language discipline, and apply parenting knowledge obtained from the Dormitory Educator Academy. The study concludes that the quarantine program functions as a structured managerial strategy for accelerating religious character formation, discipline, and adaptation among new santri. This study contributes to Islamic educational management by highlighting how leadership, habituation, instructional design, and teacher modeling can be integrated to strengthen character education in pesantren contexts.